Television and its viewers : cultivation theory and research - Shanahan, James (Cambridge University Press, 1999)
Television and its Viewers reviews 'cultivation' research, which investigates the relationship between exposure to television and beliefs about the world. James Shanahan and Michael Morgan, both distinguished researchers in this field, scrutinize cultivation through detailed theoretical and historical explication, critical assessments of methodology, and a comprehensive 'meta-analysis' of twenty years of empirical results. They present a sweeping historical view of television as a technology and as an institution. Shanahan and Morgan's study looks forward as well as back, to the development of cultivation research in a new media environment. They argue that cultivation theory offers a unique and valuable perspective on the role of television in twentieth-century social life. Television and its Viewers, the first book-length study of its type, will be of interest to students and scholars in communication, sociology, political science and psychology and contains an introduction by the seminal figure in this field, George Gerbner